2016
DOI: 10.2217/nnm-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Conjugated Magnetic Nanoparticles for Magnetically Mediated Energy Delivery to Lung Cancer Cells

Abstract: Aim:In the present study, we examine the effects of internalized peptide-conjugated iron oxide nanoparticles and their ability to locally convert alternating magnetic field (AMF) energy into other forms of energy (e.g., heat and rotational work). Materials & methods: Dextran-coated iron oxide nanoparticles were functionalized with a cell penetrating peptide and after internalization by A549 and H358 cells were activated by an AMF. Results: TAT-functionalized nanoparticles and AMF exposure increased reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 63 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…The alternating magnetic field is the most commonly used due to its large penetration. Hilt et al showed that peptide-conjugated magnetic nanoparticles (TAT-IONP) could increase cellular ROS generation in both A549 and H358 cell lines upon exposure to an alternating magnetic field, resulting in an increase in apoptosis via the Caspase 3/7 pathways (Hauser et al, 2016a ). Orel et al designed magnetic nanodots composed of doxorubicin-loaded Fe 3 O 4 nanoparticles, which could release more free iron to promote the formation of highly reactive oxygen species combined with electromagnetic fields, achieving remote modulation of redox state of Walker-256 carcinosarcoma tumor for cancer nanotherapy (Orel et al, 2018 ).…”
Section: Ferrite-based Ros-mediated Cancer Therapymentioning
confidence: 99%
“…The alternating magnetic field is the most commonly used due to its large penetration. Hilt et al showed that peptide-conjugated magnetic nanoparticles (TAT-IONP) could increase cellular ROS generation in both A549 and H358 cell lines upon exposure to an alternating magnetic field, resulting in an increase in apoptosis via the Caspase 3/7 pathways (Hauser et al, 2016a ). Orel et al designed magnetic nanodots composed of doxorubicin-loaded Fe 3 O 4 nanoparticles, which could release more free iron to promote the formation of highly reactive oxygen species combined with electromagnetic fields, achieving remote modulation of redox state of Walker-256 carcinosarcoma tumor for cancer nanotherapy (Orel et al, 2018 ).…”
Section: Ferrite-based Ros-mediated Cancer Therapymentioning
confidence: 99%
“…Conventionally, SPIONs are destined for subcutaneous or intravenous administration [ 19 ]. However, in the case of lung cancer, pulmonary delivery of the drug is more effective, allows for the reduction of systemic toxicity of the treatment and increases patients’ compliance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dextran-coated IONPs were functionalized with a cell penetrating peptide and used to inhibit the excessive formation of ROS for the treatment of lung cancer [21]. In recent years, several possible functionalizing agents, such as poly(acrylic-co-maleic), poly(trolox ester) polymers, natural antioxidants (quercetin, curcumin,green tea polyphenols, and anthocyanins),ascorbic, citric, humic, gallic, and polyacrylic acids have also been used to functionalize the bare surface of IONPs to improve colloidal stability and surface properties [20][21][22][23]. Among these surface functionalizing agents, poly(acrylic acid) (PAA) provides both electrostatic and steric repulsions against particles to stabilize their dispersion via surface functionalization of bare IONPs [24].…”
Section: Introductionmentioning
confidence: 99%